THE SCHOOL-FAMILY PARTNERSHIP FOR EFFICIENT TEACHING OF CHILDREN WITH LEARNING DISABILITIES - CORNELIA STAN (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. Belonging to a particular social group or having a certain level of development should not be arguments for the exclusion of children from mainstream schools. The integrationist movement supports the contention according to which mainstreaming provides the most appropriate environment for quality educational achievements and for acquiring social and cognitive skills. To facilitate the integration of children with learning disabilities in mainstream schools, it is necessary that these schools ensure a friendly atmosphere and real integration. Yet, active family involvement in training and education of their own children should be considered as well.